2022
DOI: 10.1155/2022/1750132
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bone Metastases by 68Ga‐DOTA‐SSAs and 18F‐FDG PET/CT: A Two‐Center Head‐to‐Head Study of Gastroenteropancreatic Neuroendocrine Neoplasms

Abstract: Purpose. This study aimed to assess the efficacy of dual-tracer [68Ga-DOTA-somatostatin receptor analogs (SSAs) and 18F-fluorodeoxyglucose (FDG)] positron emission tomography/computed tomography (PET/CT) imaging for detecting bone metastases (BMs) in patients with gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs). Methods. We retrospectively enrolled 74 GEP-NEN patients with BMs from two centers, who underwent dual-tracer PET/CT from January 2014 to March 2021. We compared and analyzed effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It may be particularly useful during surveillance, as receptor-based imaging alone may fail to show the change in tumour behaviour over time [ 76 ]. Finally, dual imaging could also be useful in detecting bone metastases that can be missed on 18F-FDG/PET alone in less differentiated GEP-NENs, as 68Ga-DOTATATE seems to be more accurate in detecting bone metastases regardless of the differentiation of the primary GEP-NEN [ 82 ].…”
Section: Morphologic Heterogeneity In Gep-nensmentioning
confidence: 99%
“…It may be particularly useful during surveillance, as receptor-based imaging alone may fail to show the change in tumour behaviour over time [ 76 ]. Finally, dual imaging could also be useful in detecting bone metastases that can be missed on 18F-FDG/PET alone in less differentiated GEP-NENs, as 68Ga-DOTATATE seems to be more accurate in detecting bone metastases regardless of the differentiation of the primary GEP-NEN [ 82 ].…”
Section: Morphologic Heterogeneity In Gep-nensmentioning
confidence: 99%
“…22 Tian et al demonstrated that [ 68 Ga]Ga-DOTA-SSA imaging performed better than [ 18 F]fluorodeoxyglucose ([ 18 F]FDG) in lesion detection and radiopharmaceutical uptake, especially in G3 NETs. 23 SSTR2 holds immense potential in the early diagnosis, staging, and prognostic evaluation of NETs.…”
Section: Sstr2mentioning
confidence: 99%
“…In 2017, SNMMI proposed [ 68 Ga]­Ga-labeled somatostatin analogue (SSA) positron emission tomography (PET)/CT imaging as the gold standard for clinical NET diagnosis, which exhibited high sensitivity for detecting primary and metastatic lesions . Tian et al demonstrated that [ 68 Ga]­Ga-DOTA-SSA imaging performed better than [ 18 F]­fluorodeoxyglucose ([ 18 F]­FDG) in lesion detection and radiopharmaceutical uptake, especially in G3 NETs . SSTR2 holds immense potential in the early diagnosis, staging, and prognostic evaluation of NETs.…”
Section: Nuclear Theranostic Probementioning
confidence: 99%
“…Since 90% of NENs show somatostatin receptors, nuclear medicine examination methods are of great importance in the diagnosis of NENs [3,14]. Somatostatin receptors can be detected via somatostatin receptor scintigraphy and, more recently, by means of 68Gallium-DOTA-TOC/-NOC/-TATE positron emission tomography (PET) [15,16]. Nuclear medicine diagnostics are of therapeutic relevance because foci showing an uptake can be treated with biological therapy with somatostatin analogs and radioreceptor therapy with gallium-or lutetium-labeled somatostatin analogs [17,18].…”
Section: Imagingmentioning
confidence: 99%